(untitled) (Homoeopathy for All, 2024)
Urticaria is an itchy rash associated with localized swelling (angioedema) on the skin that usually lasts for few hours to days before fading away. It is also known as hives. =Urticaria also called nettle-rash or hives or wheals in a common language, simply means itching with rash. Medically, urticaria may be defined as skin eruption, which is allergic in origin and is characterized by profound itching, red, circular or irregularly shaped eruptions on any part of the body. Urticaria is an allergic skin disorder. Characteristically the skin eruptions are erythematous, raised above the skin level, with intense itching and usually worsened by itching and with slight local warmth.